2021
DOI: 10.3390/ijerph18052683
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Induced Blood-Brain Barrier Impairment: An In Vitro Study

Abstract: In recent years, alcohol abuse has dramatically grown with deleterious consequence for people’s health and, in turn, for health care costs. It has been demonstrated, in humans and animals, that alcohol intoxication induces neuroinflammation and neurodegeneration thus leading to brain impairments. Furthermore, it has been shown that alcohol consumption is able to impair the blood–brain barrier (BBB), but the molecular mechanisms underlining this detrimental effect have not been fully elucidated. For this reason… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…For instance, Carrino et al. (2021) reported that multiple brain cortical regions (including the right orbitofrontal, right temporal pole, and left lateral occipital) were affected by young adults drinking alcohol, and were mainly expressed as changes to cortical gyrification. Morris et al.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Carrino et al. (2021) reported that multiple brain cortical regions (including the right orbitofrontal, right temporal pole, and left lateral occipital) were affected by young adults drinking alcohol, and were mainly expressed as changes to cortical gyrification. Morris et al.…”
Section: Introductionmentioning
confidence: 99%
“…[ 73 ] Heavy alcohol consumption, conversely, can worsen I/R injury by promoting inflammation. [ 8 , 73 ] Similarly, acute opioid administration in low doses before cortical ischemic insult has been found in mice to be neuroprotective by mitigating oxidative stress and inflammation. [ 15 ] However, in animal models, chronic opioid use in which tolerance and dependence are present can alter BBB homeostasis through a pro-inflammatory mechanism and ROS-mediated toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The following days, the cells were treated in starvation medium and, after stimulation, the medium was removed and the cells were loaded with 5 μM CM-H 2 DCFDA (Life Technologies, ThermoFisher Scientific, Milan, Italy) as previously reported. 13 …”
Section: Methodsmentioning
confidence: 99%